Association of different electrocardiographic patterns with shock index, right ventricle systolic pressure and diameter, and embolic burden score in pulmonary embolism - Krća, Bojana; Džudović, Boris; Vukotić, Snježana; Ratković, Nenad; Subotić, Bojana; Vraneš, Danijela; Rusović, Siniša; Obradović, Slobodan (Vojnosanitetski pregled, 2017)
Background/Aim. Some electrocardiographic (ECG) patterns are characteristic for pulmonary embolism but exact meaning of the different ECG signs are not well known. The aim of this study was to determine the association between four common ECG signs in pulmonary embolism [complete or incomplete right bundle branch block (RBBB), S-waves in the aVL lead, S1Q3T3 sign and negative T-waves in the precordial leads] with shock index (SI), right ventricle diastolic diameter (RVDD) and peak systolic pressure (RVSP) and embolic burden score (EBS). Methods. The presence of complete or incomplete RBBB, S waves in aVL lead, S1Q3T3 sign and negative T-waves in the precordial leads were determined at admission ECG in 130 consecutive patients admitted to the intensive care unit of a single tertiary medical center in a 5-year period. Echocardiography examination with measurement of RVDD and RVSP, multidetector computed tomography pulmonary angiography (MDCT-PA) with the calculation of EBS and SI was determined during the admission process. Multivariable regression models were calculated with ECG parameters as independent variables and the mentioned ultrasound, MDCT-PA parameters and SI as dependent variables. Results. The presence of S-waves in the aVL was the only independent predictor of RVDD (F = 39.430, p < 0.001; adjusted R2 = 0.231) and systolic peak right ventricle pressure (F = 29.903, p < 0.001; adjusted R2 = 0.185). Negative T-waves in precordial leads were the only independent predictor for EBS (F = 24.177, p < 0.001; R2 = 0.160). Complete or incomplete RBBB was the independent predictor of SI (F = 20.980, p < 0.001; adjusted R2 = 0.134). Conclusion. In patients with pulmonary embolism different ECG patterns at admission correlate with different clinical, ultrasound and MDCT-PA parameters. RBBB is associated with shock, S-wave in the aVL is associated with right ventricle pressure and negative T-waves with the thrombus burden in the pulmonary tree.
Keywords: pulmonary embolism; electrocardiography; diagnosis; differential; tomography; angiography; ventricular function; right; sensitivity and specificity